Primary localized bladder amyloidosis with negative postoperative Congo red staining: A case report - Yuchong Qiu; Sicheng Wu; Jianyang Lv; Zhigang Ji; Jie Dong (Urology Case Reports)
Localized bladder amyloidosis is a rare disorder mimicking bladder tumor, with merely over 200 reported cases. Here, we report a case of a 67-year-old female presented with painless gross hematuria. A positive Congo red staining of the cystoscopy biopsy raised suspicion of bladder amyloidosis, and transurethral resection of the mass was performed. Interestingly, the histopathology of the excised mass showed pink-staining material under Hematoxylin and Eosin staining, but negative Congo red staining. This case demonstrates that a negative Congo red staining doesn't exclude amyloidosis. An accurate diagnosis should rely on a comprehensive evaluation of clinical, laboratory, radiological, and histopathological findings.